Sociolinguistic Features of Novelistic Speech - Kholikova, Nazokat Batirovna (International Journal of Formal Education, 2024)
Sociolinguistic features of novelistic speech encompass the diverse ways in which characters' dialogue reflects social structures, identities, and power dynamics. This study delves into the intersection of sociolinguistics and literary analysis, focusing on how authors use language to construct and convey social realities within their narratives. By examining a selection of contemporary and classic novels, this research identifies key sociolinguistic markers such as dialect, register, code-switching, and speech acts that authors deploy to differentiate characters based on their social class, ethnicity, gender, and other sociocultural factors. The analysis reveals that novelistic speech serves not only as a vehicle for character development and plot progression but also as a medium for social commentary. Authors often employ linguistic variation to highlight social hierarchies and tensions, thereby enriching the reader's understanding of the fictional world and its parallels to real-life social dynamics. Furthermore, the study explores the impact of narrative voice and perspective on the representation of sociolinguistic diversity, demonstrating how first-person and omniscient narrators differently navigate and present linguistic variation. By situating novelistic speech within the broader framework of sociolinguistic theory, this research contributes to a more nuanced appreciation of the literary function of language and underscores the importance of linguistic analysis in literary studies. The findings underscore the intricate relationship between language and society, illustrating how novels can both reflect and shape readers' perceptions of social realities.